Effects of CFD parameter variation on tidal energy resource assessment - Abundo, Michael Lochinvar Sim (2013)
Accurate tidal in-stream energy resource estimation is very important for planning purposes. Hydrodynamic simulations using computational fluid dynamics (CFD) is commonly employed in the assessment of candidate sites for tidal energy extraction. The estimated energy of a site using simulations may vary as certain CFD parameters change. This work studies the effects of varying grid size (x, y, and z) and boundary conditions (number of tidal constituents and amplitudes) on the current velocities' magnitude (histogram) and direction, and ultimately the estimated energy. A sensitivity analysis of the changes in tidal energy resource estimate as a result of simulation parameter variations is presented. The trade-off between accuracy and computational resource used is also presented. Results indicate that energy resource estimates are affected by the variation of the investigated parameters in the following order of significance: grid (x, y), number of boundary conditions, amplitude of boundary conditions, and computing layer (z).